Autobiographical Discourse in South Asian Feminist Literature: A Paratextual Analysis of Narrative Strategies of Memory and Resistance - Nasution, Aulia Muflih; Selfira, Sakina (Journal of Research in Vocational Education, 2025)
This study explores the autobiographical tradition in Indian women's literature, focusing on Kamala Das and Amrita Pritam. It examines how their narratives challenge patriarchal norms and redefine female identity through self-expression. The paper highlights how autobiography serves as a vehicle for personal and social transformation, providing an in-depth analysis of select works. By contextualizing these writings within feminist literary discourse, the study underscores their significance in reshaping perspectives on gender, identity, and literary self-representation.